DOI: 10.11606/t.8.2022.tde-30092022-144145
|View full text |Cite
|
Sign up to set email alerts
|

Representação política e conexão territorial: uma etnografia de vereadores e >i<brokers>/i< em São Paulo

Abstract: Este trabalho não poderia ter sido realizado sem a colaboração, paciência e disposição ao diálogo das pessoas que se tornaram minhas interlocutoras no campo. O imperativo de preservar suas identidades me impede de nomeá-las aqui, mas a todas elas, minha admiração e profunda gratidão pelo que me ensinaram ao longo desses anos de convívio.O resultado desta tese é também fruto da minha inserção em diferentes âmbitos da vida. Aproveito a oportunidade para reconhecer a trajetória que me trouxe até aqui e expressar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 58 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…These recent works review and expand previous research on politics in Latin American cities, which explained the roots of clientelism among the urban poor (Auyero 2000), and the varying types of relations between informal settlement dwellers and politicians (Gay 1994). As the quid pro quo typically equated to clientelism is rarely found in empirical accounts (Hicken and Nathan 2020), scholars underscore the lack of conceptual fit and explore the persistence of nonprogrammatic politics in varied and complex local arrangements (Rivadulla 2012;Hoyler 2022), revealing that legislators and other politicians may provide constituency services to allow citizens to benefit from services they are entitled to but can hardly access (Bussell 2019;Hoyler 2022). As Heller and colleagues (2023, 84) argue, research on brokerage may thus benefit from differentiating between "(a) highly dependence-inducing and autonomy-eroding (classic clientelism), (b) asymmetrical but strategic and competitive, or in fact (c) approximates [of ] constituency service," considering their divergent consequences for democracy.…”
Section: Brokerage For Services and Land Tenure In Global South Citiesmentioning
confidence: 73%
See 1 more Smart Citation
“…These recent works review and expand previous research on politics in Latin American cities, which explained the roots of clientelism among the urban poor (Auyero 2000), and the varying types of relations between informal settlement dwellers and politicians (Gay 1994). As the quid pro quo typically equated to clientelism is rarely found in empirical accounts (Hicken and Nathan 2020), scholars underscore the lack of conceptual fit and explore the persistence of nonprogrammatic politics in varied and complex local arrangements (Rivadulla 2012;Hoyler 2022), revealing that legislators and other politicians may provide constituency services to allow citizens to benefit from services they are entitled to but can hardly access (Bussell 2019;Hoyler 2022). As Heller and colleagues (2023, 84) argue, research on brokerage may thus benefit from differentiating between "(a) highly dependence-inducing and autonomy-eroding (classic clientelism), (b) asymmetrical but strategic and competitive, or in fact (c) approximates [of ] constituency service," considering their divergent consequences for democracy.…”
Section: Brokerage For Services and Land Tenure In Global South Citiesmentioning
confidence: 73%
“…The local government carries on a policy of land regularization for low-income communities, granting titles to households in favelas and irregular subdivisions (Marques and Pulhez 2021). In the city, brokerage is a common practice adopted by municipal councilors to provide services-including land regularization-to their constituencies and build political representation (Hoyler 2022). These municipal legislators intermediate citizens' demands for land tenure security and push the housing bureaucracy to deliver land titles to the informal settlements among their electorate.…”
mentioning
confidence: 99%
“…A series of works has explored the relationship between such rituals and the efforts to constitute the State (see Anderson, 1983;Hobsbawm & Ranger, 1997;Gupta, 2012;Hull, 2012;Riles, 2006)). The role of the rites lies precisely in the effect that their repeated mobilisation and formalization has on constituting a tradition able to sediment an official history as we have argued in Hoyler andCampos (2019) -or, as Pinto (2013: 20) suggests, a form of inventing history, "since they become 'crystalized' in official documents and may (or may not) be mobilised to tell the history of cities, the nation, a government or the legislative power. "…”
Section: Pedro Campos and Telma Hoylermentioning
confidence: 99%
“…As the author further remarks, the importance of the rites also resides in their effects on the actors involved in their production and reproduction. Other works that examine the topic either directly (Pinto, 2013) or indirectly (Kuschnir, 2000;Hoyler, 2022) have shown that, through the distributions of tributes and commendations, councillors make evident who forms part of their political group and try to become more closely associated with those they wish to link with their image. This set of actions, therefore, is among the array of activities responsible for constituting and mobilizing networks of support for politicians and their mandates.…”
Section: Pedro Campos and Telma Hoylermentioning
confidence: 99%
See 1 more Smart Citation